MR-Guided Radiotherapy for Rectal Cancer: Current Perspective on Organ Preservation - Boldrini, Luca; Intven, Martijn; Bassetti, Michael; Valentini, Vincenzo; Gani, Cihan (Frontiers in Oncology, 2021)
Online magnetic resonance imaging guided radiotherapy (MRgRT) is one of the most recent technological advances in radiotherapy. MRgRT permits both the visualization of tumor and healthy tissue while the patient is on the treatment table and online daily plan adaptations following the observed anatomical changes. In the context of rectal cancer, online MRgRT is a very promising modality due to the pronounced geographical variability of tumor and surrounding healthy tissues. This current perspective paper will discuss possible applications of online MRgRT in particular in terms of radiotherapy dose escalation and response prediction in organ preservation approaches for rectal cancer.